Clinicopathological study of neck mass in pediatric age group - Ray, Ritam; Sarkar, Shaswata; Bhattacharyay, Aditi (Asian Journal of Medical Sciences, 2023)
Background: Neck swellings are common in clinical practice and are of various types – congenital, acquired, inflammatory, neoplastic, and miscellaneous. The workup of a neck mass is different in children and adults, as the etiologies are different. Only 2–15% are malignant. Aims and Objectives: To estimate the burden of neck mass in pediatric age group clinicopathological. Materials and Methods: This prospective observational study was conducted in the Otorhinolaryngology Department of Burdwan Medical College and Hospital, Burdwan, a rural-based tertiary care hospital in Burdwan for 18 months from April 2021 to September 2022, and 50 patients in pediatric age group presented with neck swelling were included in this study after through history taking and meticulous clinical examination and after getting institutional ethics committee clearance. Results: It was found that most of the patients presented with swelling over the right side (26 [52.0%]), but this was not statistically significant (P=68916) (Z=0.4). Few patients had (11 [22.0%]) 5 months of duration of symptoms, but it was not statistically significant (P=63836) (Z=0.4683). Some of the patients had fever and cough (13 [26.0%]) which was statistically significant (P<0.00001) (Z=4.8). Conclusion: This study revealed the demographic and clinic-pathological profile of neck mass of various pathologies in pediatric age group.